2006
DOI: 10.1007/s00213-006-0492-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the amnesic drug lorazepam on complete and partial information retrieval and monitoring accuracy

Abstract: When studying four-letter nonsense letter strings, lorazepam participants present an impairment of episodic short-term memory and the drug has an effect on FOK estimates but not on the predictive accuracy of the FOK. The accessibility hypothesis of FOK was confirmed in this study and seems to retain some validity even under the effect of an amnesic drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…P. Carter, Kleykamp, et al, 2013;L. P. Carter, Reissig, et al, 2013;Kleykamp et al, 2012;Mintzer et al, 2010;Mintzer & Griffiths, 2003a, 2003b, though not always (Izaute & Bacon, 2006;Kleykamp et al, 2010;Mintzer & Griffiths, 2005). Considering the massive amnestic effects of these drugs, it should be unsurprising that a measure of metamemory that is correlated with memory accuracy would also exhibit a reduction.…”
Section: Sedatives (γ-Aminobutyric Acid a Receptor Positive Allosteri...mentioning
confidence: 99%
“…P. Carter, Kleykamp, et al, 2013;L. P. Carter, Reissig, et al, 2013;Kleykamp et al, 2012;Mintzer et al, 2010;Mintzer & Griffiths, 2003a, 2003b, though not always (Izaute & Bacon, 2006;Kleykamp et al, 2010;Mintzer & Griffiths, 2005). Considering the massive amnestic effects of these drugs, it should be unsurprising that a measure of metamemory that is correlated with memory accuracy would also exhibit a reduction.…”
Section: Sedatives (γ-Aminobutyric Acid a Receptor Positive Allosteri...mentioning
confidence: 99%
“…Several studies have found that sedatives at encoding impair metamemory (Bacon et al, 1998;Mintzer and Griffiths, 2003a;b, 2007;Carter et al, 2009;Mintzer et al, 2010;Kleykamp et al, 2012;Carter, Kleykamp, et al, 2013;Carter, Reissig, et al, 2013), though not always (Mintzer and Griffiths, 2005;Izaute and Bacon, 2006;Kleykamp et al, 2010). However, all of these studies used gamma and are therefore susceptible to response bias confounds and memory accuracy scaling with this measure of metamemory.…”
Section: Sedatives (Gabaa Pams)mentioning
confidence: 99%